Development of Natural Resources Magazine (Majasda) to Increase Reading Interest of Elementary School Students - Fadhek Lianingsih; Dwi Kameluh Agustina; Sripit Widiastuti (Universitas Islam Balitar, 2021)
Based on the results of observations at UPT SDN Sumberjo 02, it is known that the learning books used are less varied, so creative and interesting reading books are needed. At that school the Natural Resources Magazine (Majasda) had never been used. The purpose of this study is to explain the development of Majasda and increase the reading interest of elementary school students. The research design used is R&D, namely research and development. The research and development model used is Borg and Gall proposed by Sugiyono, which is only limited to the seventh stage, namely product revision. The results showed that the assessments of media experts, linguists and material experts were respectively 85.5%, 84.16% and 80%. 94% student response. Students' reading interest increased by 99%, from the average result of 2.63 to 5.27. The results of the study got a percentage of 9,99% student reading interest questionnaire. So it is known that Majasda can increase the reading interest of elementary school students.